Pengembangan Media Website Tahfidz Al–Quran di Pondok Pesantren Nurul Iman Al–Hasanah Kabupaten Bogor pada Jenjang SMP - Asidiqi, Khudri (Program Studi Manajemen Pendidikan Islam, 2024)
The objectives of this research are: (1) to develop a website-based learning media for Quran memorization (Tahfidz) for junior high school students at Pondok Pesantren Nurul Iman Al-Hasanah in Bogor Regency, and (2) to evaluate the results of expert validation on the Quran memorization website learning media at Pondok Pesantren Nurul Iman Al-Hasanah in Bogor Regency for junior high school students. This research is classified as Research and Development (R&D) using the ADDIE development model. The research subjects are male students aged 12–15 years. Data collection techniques include interviews, documentation, and questionnaires administered to experts and students, utilizing both quantitative and qualitative data. The results of the expert validation trials show that: (1) the media expert's assessment was 83.9%, (2) the material expert's assessment was 76.6%, and (3) the instructional design expert's assessment was 87.5%, indicating that the website-based Quran memorization learning media falls into the